Social Change, Communication of Ideas, and Library Service with Special Reference to Developing Societies - Neelameghan, A. (Journal of Information and Knowledge, 1973)
Attributes of a developing society undergoing socio-economic change, and the characteristics which enable it to generate change and to adapt itself to continuously changing economic, social, and political demands, perpetuation, are briefly discussed, Concepts such as modernisation, development, dynamism, democracy, science-based social development, and sovereignty are explained. The socio-economic disparity among nations, and the stresses and strains of modernisation in a developing society are highlighted. The transfer of culture through communication is shown to be a basic behavioural characteristic of human beings and that it has survival value for the species. The need to view communication of ideas and innovation among people in the perspective of the social system in which it takes place is emphasised. The variety of attributes of the communicator and of the communicatee, of the medium and mode of communication, and of the environment as a whole are enumerated and their effects on the communication of ideas are mentioned. The barriers to communication, particularly the culture, are highlighted. The role of library service in keeping democracy safe, in promoting universal education, in supporting higher education and research, int adult literacy and social education programmes, in preserving amity among nations, and in industrial development and technology transfer, is discussed. The future of information service is outlined quoting from a Delphi study.